Canalicular lacerations: causes, associated ocular injuries, and audit of management at St John Eye Hospital - Lindeque, Stephanus J. (My University, 2020)
Background: Canalicular lacerations cause significant morbidity if unrepaired, and may be associated with serious ocular injuries. Few studies describe the causes of these injuries, and none of these were conducted in Southern Africa. Aim: This study’s aim was to describe the incidence of canalicular lacerations in terms of their causes, associated ocular injuries, and management at St John Eye Hospital. Setting: St John Eye Hospital, Soweto, Gauteng, South Africa. Methods: This was a prospective descriptive study of all patients presenting with canalicular lacerations at St John Eye Hospital over a seven month period. Data was collected from the patient files and analysed using descriptive statistics.Results: 78 patients presented at St John Eye Hospital with lid lacerations. Of these 78 patients, 26 (33.3%) had canalicular involvement. There was only slight male preponderance. The median age was 34 years. The most common cause of injury was assault (58%) usually involving a knife. 35% of the patients had an associated ocular injury. Globe rupture was relatively common (8%). All patients received lid repair under general anaesthetic. 19% received additional surgical procedures. The median duration of surgery was 103 minutes. Canalicular repair consumed 100 minutes of operating time per week. Conclusion: This study demonstrates that canalicular lacerations are relatively common at St John Eye Hospital. They are disproportionately caused by assault, and more often associated with serious ocular injuries than expected. They place considerable burden on already limited theatre resources, and may be of particular relevance in the South African setting.
A research report submitted in fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020